Deteksi Pengetahuan Politik Pemilih Pemula Mahasiswa Dalam Pemilihan Calon Walikota Pekanbaru Tahun 2024-2029 - Darmansyah, Ramlan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
Detection of political knowledge of novice student voters in the regional head election process for candidates for Mayor and Deputy Mayor of Pekanbaru in 2024-2029, intend to describe research findings related to the political knowledge of novice voters in the context of regional head elections which are one of the phenomena of local politics and local democracy. The research method used in this research study process is qualitative description, namely research that describes research data through interviews using Google form media. The informants in this research are students who are beginner voters aged 17 to 22 years. The detection results found in this research are, on average students who are categorized as beginner voters are students who are in their first semester of college who have never used their voting rights. Students' knowledge as novice voters in the election of candidates for Mayor and Deputy Mayor of Pekanbaru can be said to be good, by obtaining information from promotional media for regional head candidates, namely billboards and social media. Students' political interest in the contestation for the election of candidates for Mayor and Deputy Mayor of Pekanbaru can also be considered very good.